Strategic Triangle in the Indo-Pacific Region through Competition, Cooperation and Containment: Future of Maritime Power Posturing - Dr. Muhammad Sharreh Qazi (Journal of Political Studies, 2021)
Within bounds of the Regional Security Complex, this article assesses key developments in the Indian Ocean and fallout of strategic interests from the Pacific Ocean in maritime convergence. The article argues that maritime interests in the Indian and Pacific Ocean are witnessing convergence as states form coalitions and strategic partnerships to create a balance between USA and China. Strategic choices between principal and peripheral actors is structured in a mix of containment, competition and cooperation. China and its strategic partners understand the momentum of impact if American interests in the Pacific Ocean are merged with its interests in the Indian Ocean. The article argues that China would be opting to go for cooperation strategy as a means to broaden its reach and entangle oncoming contenders. America, on the other hand, is opting to amalgamate both competition and containment in a worst case scenario situation to prevent China from creating an overwatch against global maritime activity. The paper finds that an escalatory environment with spiraling tendencies is forming in and around the Indo-Pacific and its fallout will likely be seen in assessment of magnitude of contending parties. It finds that despite understanding maritime worth of the Indo-Pacific connect, principal and peripheral partners to these strategies might be willing to transform maritime politics to strategic entanglement.